2005
DOI: 10.1088/0953-8984/17/9/022
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and dewetting of extracellular matrix and glycocalix models

Abstract: In this paper, we study wetting and dewetting of hydrated biopolymer layers mediating cell-cell and cell-tissue contacts, called the extracellular matrix and cell surface glycocalix, by the combination of various physical techniques. Here, the sum of the net effects of the various interfacial forces, which is referred to as the disjoining pressure, is used as a semi-quantitative measure to describe the thermodynamics of hydrated interlayers. The disjoining pressure can be measured by applying external forces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Polyethylene glycol (PEG), cellulose and dextran are among the most commonly used polymers for making polymer cushioned SLB [6974]. A hydrated polymer cushion acts as a spacer and a lubricating layer between the lipid bilayer and the substrate and assists self-healing of local membrane defects [75,76]. In addition to a cushioning polymer film, alternative strategies include self-assembled monolayers (SAMs) [77,78] and the use of adsorbed or bound proteins as a cushioning layer [7983].…”
Section: Experimental Lipid Nanotechnologymentioning
confidence: 99%
“…Polyethylene glycol (PEG), cellulose and dextran are among the most commonly used polymers for making polymer cushioned SLB [6974]. A hydrated polymer cushion acts as a spacer and a lubricating layer between the lipid bilayer and the substrate and assists self-healing of local membrane defects [75,76]. In addition to a cushioning polymer film, alternative strategies include self-assembled monolayers (SAMs) [77,78] and the use of adsorbed or bound proteins as a cushioning layer [7983].…”
Section: Experimental Lipid Nanotechnologymentioning
confidence: 99%
“…[4,[15][16][17] The concept of such ''polymer-supported'' membranes can be realized by intermediate ''polymer cushions'' [15,[18][19][20][21] or ''polymer-tethered'' membranes (PTM). In the latter, lipids with hydrophilic polymer head groups (lipopolymers) are incorporated into the lipid bilayer, acting as spacer to define the distance between membrane and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…At thermal equilibrium, the disjoining pressure counterbalances the osmotic pressure. 18,41 For the measurements in bulk buffers, 19,20 a self-built liquid cell consisting of two Si wafers with a gap of 0.17 mm was used. To guarantee that the sample reaches the equilibrium state, the sample was held at each temperature and humidity condition for at least 90 min before measurement.…”
Section: Sample Environmentmentioning
confidence: 99%
“…15,16 As the surface of eukaryotic and prokaryotic cells is coated with saccharide chains that serve as a) Authors to whom correspondence should be addressed. Electronic addresses: ayamamoto@icems.kyoto-u.ac.jp and tanaka@uni-heidelberg.de protectors to sustain the structural integrity as well as specific ligands for proteins and complementary saccharides, 17,18 we have previously proposed more realistic model systems based on synthetic and natural glycolipids. [19][20][21] We demonstrated that the introduction of finite size effects, the so-called "cut-off radius," 22 allows full calculation of the scattering functions in reciprocal space and quantification of the vertical compression modulus B and the bending rigidity κ of the membranes.…”
Section: Introductionmentioning
confidence: 99%